Analisis Karakteristik Pengguna Jalan Di Kota Batam - Gabriel Bryan; Yusra Aulia Sari (Jurnal Ilmiah Rekayasa Sipil, 2022)
Human life is inevitable from the need for transportation which is used as a supporting tool to fulfill and facilitate humans to their desired destinations. Transportation which is also a necessity for the people of Batam City has an influence on the condition of road users on almost every side of Batam City which can be found by various road users with their respective vehicles. Characteristics are individual behaviors and actions that must be considered, especially for road users. Users of this road have a variety of characteristics since many people pass by around Gajah Mada Road, Batam City depending on the purposes and needs of each person. The purpose of this research is to analyze the characteristics of road users, analyze the grouping of road user characteristics, analyze the impact of road users through road user characteristics, and find out the number of users of the Gajah Mada Road, Batam City. The research methods used are qualitative and quantitative approaches, the primary data collection techniques are in the form of questionnaires, while secondary data are observations and literature reviews from previous research. The results showed that there is a diversity of characteristics of road users at Gajah Mada Road, Batam City such as road users who always obey traffic signs and lights; the characteristic behaviors of breaking rules are considered neutral; as well as the completeness of driver’s license. Therefore, the researcher wants to discuss the characteristics of these road users.